Integration of computational modeling with membrane transport studies reveals new insights into amino acid exchange transport mechanisms. Issue 6 (11th March 2015) - Widdows, Kate L.; Panitchob, Nuttanont; Crocker, Ian P.; Please, Colin P.; Hanson, Mark A.; Sibley, Colin P.; Johnstone, Edward D.; Sengers, Bram G.; Lewis, Rohan M.; Glazier, Jocelyn D.
ABSTRACT: Uptake of system L amino acid substrates into isolated placental plasma membrane vesicles in the absence of opposing side amino acid ( zero‐trans uptake) is incompatible with the concept of obligatory exchange, where influx of amino acid is coupled to efflux. We therefore hypothesized that system L amino acid exchange transporters are not fully obligatory and/or that amino acids are initially present inside the vesicles. To address this, we combined computational modeling with vesicle transport assays and transporter localization studies to investigate the mechanisms mediating [ 14 C]l ‐serine (a system L substrate) transport into human placental microvillous plasma membrane (MVM) vesicles. The carrier model provided a quantitative framework to test the 2 hypotheses that l ‐serine transport occurs by either obligate exchange or nonobligate exchange coupled with facilitated transport (mixed transport model). The computational model could only account for experimental [ 14 C]l ‐serine uptake data when the transporter was not exclusively in exchange mode, best described by the mixed transport model. MVM vesicle isolates contained endogenous amino acids allowing for potential contribution to zero‐ trans uptake. Both L‐type amino acid transporter (LAT) 1 and LAT2 subtypes of system L were distributed to MVM, with L‐serine transport attributed to LAT2. These findings suggest that exchange transporters do not function exclusively as obligate exchangers.—Widdows, K. L., Panitchob, N., Crocker, I. P., Please, C. P., Hanson, M. A., Sibley, C. P., Johnstone, E. D., Sengers, B. G., Lewis, R. M., Glazier, J. D. Integration of computational modeling with membrane transport studies reveals new insights into amino acid exchange transport mechanisms. FASEB J. 29, 2583‐2594 (2015). www.fasebj.org